11th FORM STUDENTS’ MOTIVATION FOR DOING ENGLISH HOMEWORK AT NGUYEN GIA THIEU HIGH SCHOOL - Phạm, Thu Hà (2020)
In the light of the 11th form students‟ motivation for doing English homework at Nguyen Gia Thieu High School, this study investigates the extent to which the students are intrinsically and extrinsically motivated and also examines the demotivating factors to the students‟ homework completion. One hundred and thirty six students of grade 11 participated in completing a questionnaire reflecting their motives for doing English homework and what negatively affected their motivation. Follow-up interviews with two students were also conducted to deepen understanding and interpretation of the study. Results showed that the 11th form students in the three surveyed classes had a higher degree of intrinsic motivation than extrinsic one. Contrary to the findings of other related studies, it was the nature of homework but not the teacher that was in the first place in terms of affective factors to the students‟ motivation.